2022
DOI: 10.1186/s13071-022-05370-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergence dynamics of adult Culicoides biting midges at two farms in south-east England

Abstract: Background Culicoides biting midges (Diptera: Ceratopogonidae) are biological vectors of livestock arboviruses that cause diseases with significant economic, social and welfare impacts. Within temperate regions, livestock movement during arbovirus outbreaks can be facilitated by declaring a ‘seasonal vector-free period’ (SVFP) during winter when adult Culicoides are not active. In this study we carry out long-term monitoring of Culicoides adult emergence from larval development habitats at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…Although we observed similar peaks in our collected samples around weeks 17-21 in both years, the resulting coefficient estimates from our universal model show time as a significant factor in 2016 but not 2015. Similarly, Culicoides studies in England found that emergence is continual and highly variable throughout the year [60], suggesting that time in the HD season may not be the most reliable factor for predicting abundance [61]. Here, we show a more accurate predictor of biting midge abundance may be a combination of covariates such as habitat type, proximity to water, proximity to bloodmeals and soil drainage.…”
Section: Discussionmentioning
confidence: 53%
“…Although we observed similar peaks in our collected samples around weeks 17-21 in both years, the resulting coefficient estimates from our universal model show time as a significant factor in 2016 but not 2015. Similarly, Culicoides studies in England found that emergence is continual and highly variable throughout the year [60], suggesting that time in the HD season may not be the most reliable factor for predicting abundance [61]. Here, we show a more accurate predictor of biting midge abundance may be a combination of covariates such as habitat type, proximity to water, proximity to bloodmeals and soil drainage.…”
Section: Discussionmentioning
confidence: 53%
“…Culicoides biting midges (Diptera: Ceratopogonidae) are arbovirus vectors that feed on a variety of vertebrates (Stokes et al., 2022 ). Female Culicoides require mammalian blood to produce eggs, and allergic reactions to Culicoides bites are caused by immune responses to Culicoides salivary components secreted during a blood meal.…”
Section: Introductionmentioning
confidence: 99%
“…Culicoides biting midges (Diptera: Ceratopogonidae) are arbovirus vectors that feed on a variety of vertebrates (Stokes et al, 2022). Female…”
Section: Introductionmentioning
confidence: 99%